Dynamic Behavior of Clay-Aggregate Mixtures - Kang Fei; Jinxin Xu (Advances in Materials Science and Engineering)
Clay-aggregate mixtures are frequently used in engineering practice. To improve the understanding of the effects of coarse particles on the dynamic behavior of clay-aggregate mixtures, series of stress controlled cyclic triaxial tests were performed on clay specimens with various glass bead contents. The results show that the initial shear modulus of clay-aggregate mixtures increased with the increase of the coarse aggregate content and the confining stress. At the confining stress of 100, 200, and 400 kPa, the addition of 32% coarse particles caused an increase in the initial shear modulus of 117%, 110%, and 67%, respectively. Moreover, the normalized shear modulus decreased and damping ratio increased with the coarse aggregate content, and the influence of the confining stress on the strain-dependent dynamic properties was negligible. The specimen with a higher coarse aggregate content was observed to have larger cyclic shear strength and smaller excess pore water pressure, but the effects of the coarse aggregate content became less pronounced under large cyclic stresses.